Phosphatidylcholine Specific PLC-Induced Dysregulation of Gap Junctions, a Robust Cellular Response to Environmental Toxicants, and Prevention by Resveratrol in a Rat Liver Cell Model - Sovadinova, Iva; Babica, Pavel; Böke, Hatice; Kumar, Esha; Wilke, Andrew; Park, Joon-Suk; Trosko, James E; Upham, Brad L (PloS one, 2015)
UNLABELLED: Dysregulation of gap junctional intercellular communication (GJIC) has been associated with different pathologies, including cancer; however, molecular mechanisms regulating GJIC are not fully understood. Mitogen Activated Protein Kinase (MAPK)-dependent mechanisms of GJIC-dysregulation have been well-established, however recent discoveries have implicated phosphatidylcholine-specific phospholipase C (PC-PLC) in the regulation of GJIC. What is not known is how prevalent these two signaling mechanisms are in toxicant/toxin-induced dysregulation of GJIC, and do toxicants/toxins work through either signaling mechanisms or both, or through alternative signaling mechanisms. Different chemical toxicants were used to assess whether they dysregulate GJIC via MEK or PC-PLC, or both Mek and PC-PLC, or through other signaling pathways, using a pluripotent rat liver epithelial oval-cell line, WB-F344. Epidermal growth factor, 12-O-tetradecanoylphorbol-13-acetate, thrombin receptor activating peptide-6 and lindane regulated GJIC through a MEK1/2-dependent mechanism that was independent of PC-PLC; whereas PAHs, DDT, PCB 153, dicumylperoxide and perfluorodecanoic acid inhibited GJIC through PC-PLC independent of Mek. Dysregulation of GJIC by perfluorooctanoic acid and R59022 required both MEK1/2 and PC-PLC; while benzoylperoxide, arachidonic acid, 18β-glycyrrhetinic acid, perfluorooctane sulfonic acid, 1-monolaurin, pentachlorophenol and alachlor required neither MEK1/2 nor PC-PLC. Resveratrol prevented dysregulation of GJIC by toxicants that acted either through MEK1/2 or PC-PLC. Except for alachlor, resveratrol did not prevent dysregulation of GJIC by toxicants that worked through PC-PLC-independent and MEK1/2-independent pathways, which indicated at least two other, yet unidentified, pathways that are involved in the regulation of GJIC. IN CONCLUSION: the dysregulation of GJIC is a contributing factor to the cancer process; however the underlying mechanisms by which gap junction channels are closed by toxicants vary. Thus, accurate assessments of risk posed by toxic agents, and the role of dietary phytochemicals play in preventing or reversing the effects of these agents must take into account the specific mechanisms involved in the cancer process.
Keywords: Cell Line; Rats; analýza hlavních komponent; Resveratrol; fosfatidylcholiny; přemostěné cyklické sloučeniny; Bridged-Ring Compounds; resveratrol; potkani inbrední F344; Thiocarbamates; Thiones; thiokarbamáty; Type C Phospholipases; butadieny; krysa rodu Rattus; Principal Component Analysis; norbornany; Norbornanes; zvířata; fosfolipasy typu C; thioketony; stilbeny; Butadienes; Rats, Inbred F344; mezerový spoj; Phosphatidylcholines; buněčné linie; Gap Junctions; Stilbenes; nitrily; Nitriles; Animals